2004
DOI: 10.1002/jnr.20162
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced behavioral recovery and neuroplasticity in the 1‐methyl‐4‐phenyl‐1,2,3,6‐tetrahydropyridine‐lesioned mouse basal ganglia

Abstract: Physical activity has been shown to be neuroprotective in lesions affecting the basal ganglia. Using a treadmill exercise paradigm, we investigated the effect of exercise on neurorestoration. The 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-lesioned mouse model provides a means to investigate the effect of exercise on neurorestoration because 30-40% of nigrostriatal dopaminergic neurons survive MPTP lesioning and may provide a template for neurorestoration to occur. MPTP-lesioned C57 BL/6J mice were adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
226
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 278 publications
(251 citation statements)
references
References 40 publications
19
226
2
4
Order By: Relevance
“…Animal models of PD have also supported activity-dependent neuroplasticity after intensive treadmill training as measured through changes in dopamine handling and neurotransmission, including increased dopamine release, decreased uptake and an increase in the postsynaptic dopamine D2-receptor subtype within the basal ganglia. 2,60 …”
Section: Discussionmentioning
confidence: 99%
“…Animal models of PD have also supported activity-dependent neuroplasticity after intensive treadmill training as measured through changes in dopamine handling and neurotransmission, including increased dopamine release, decreased uptake and an increase in the postsynaptic dopamine D2-receptor subtype within the basal ganglia. 2,60 …”
Section: Discussionmentioning
confidence: 99%
“…For instance, like cocaine, exercise increases central dopamine concentrations (Heyes et al, 1988;Hattori et al, 1994;Meeusen et al, 1997;Petzinger et al, 2007), and these increases are positively correlated with exercise output (Freed and Yamamoto, 1985). Importantly, chronic, long-term exercise leads to sustained increases in dopamine concentrations (Bauer et al, 1989) and compensatory changes in dopamine binding proteins (Fisher et al, 2004). Studies focusing specifically on the dopamine D 2 receptor have typically reported an increase in D 2 receptor density following chronic exercise (Gilliam et al, 1984;MacRae et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, acute bouts of exercise increase central dopamine concentrations (Heyes et al, 1988;Hattori et al, 1994;Meeusen et al, 1997;Petzinger et al, 2007), and chronic exercise leads to sustained increases in dopamine concentrations and compensatory alterations in dopamine binding proteins (Gilliam et al, 1984;MacRae et al, 1987;Fisher et al, 2004). Given that many addictive drugs produce their positive-reinforcing effects by increasing dopamine transmission in mesolimbic and mesocortical pathways (Goeders and Smith, 1983;Caine and Koob, 1994;Wise et al, 1995;Pich et al, 1997), chronic exercise may produce functional changes in these pathways that leave an organism less susceptible to their positive-reinforcing effects.…”
Section: Introductionmentioning
confidence: 99%
“…In animal models of spinal cord injury, exercise has been shown to increase the release of brain-derived neurotrophic factor, which promotes reflex normalization [42], and to increase action of microRNAs, which help regulate apoptosis after injury [43]. Fisher et al showed that when neurologically damaged rats were exposed to treadmill training, their walking performance returned to the level of nondisabled control subjects within 30 days [44]. These results speak to the widespread effects that exercise may have in patients with neurological disease.…”
Section: Discussionmentioning
confidence: 99%